THE RELATIONSHIP OF TNFα -308 G/A POLYMORPHISM WITH THE INCIDENCE OF CERVICAL CANCER IN ASIAN WOMEN: A META ANALYSIS OBSERVATIONAL STUDY - Saraswati, Henny; Nurmalasari, Mieke (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2024)
Cervical cancer is a malignancy with high mortality rates in women, and its incidence continues to rise. The main etiological factor for cervical cancer is infection with Human Papillomavirus (HPV), which disrupts the regulation of apoptosis in cells. Several studies have shown a correlation between TNFα polymorphisms, including the -308 position (TNFα -308 G/A), and the incidence of cervical cancer.This gene have a role in proliferation of cancer cells. This study investigates the impact of TNFα-308 polymorphism on the risk of cervical cancer in Asian female populations. A meta-analysis of five sources was conducted to determine potential associations. Findings reveal that neither allele A (OR 95%CI = 1.20 [0.70-2.03], p = 0.51) nor genotype AA (OR 95%CI = 0.85 [0.37-1.91], p = 0.69) were significantly linked with an elevated risk of cervical cancer in Asian women. The same result was seen for the G allele (OR 95%CI = 0.84 [0.49-1.42], p = 0.51) and GG genotype (OR 95%CI = 0.80 [0.44-1.48], p = 0.48). The study results indicate that the TNFα-308 polymorphism is not associated with cervical cancer in Asian women. Further research is needed to investigate the role of other gene polymorphisms in cervical cancer susceptibility in Asian women.